Laboratory Testing-Based Characterization of Peat in Palangkaraya, Central Kalimantan - Annisa Khoerani; Iskandar; Ahmad Sofyan; Tatang Sumarna; Dewi Amalia; Dewi Amalia; Suherman Sulaiman (Technium: Romanian Journal of Applied Sciences and Technology, 2023)
Peat is a unique type of soil because it has a very high organic matter content. One of the locations in Indonesia that has the most peat distribution is Palangkaraya City, Central Kalimantan. It is important to understand the characteristics of peat, especially in engineering applications. The characteristics of peat can be known based on laboratory testing, but in practice many tests are not carried out in accordance with the characteristics of the peat. In this paper, laboratory tests will be carried out based on the characteristics of the peat, with a focus on testing the physical and mechanical properties of the soil. Based on the results of the tests conducted, it can be concluded that the Palangkaraya peat is a fibrous hemic peat. The Palangkaraya peat has a water content of 639.5%, ash content of 3.25%, organic content of 96.75%, fiber content of 53.32%, pH of 3.2, content weight of 0.983 gr/cm3, specific gravity of 1.48, cohesion value of 0.138, and inner shear angle of 16.26°. The characteristics of this peat can provide an overview for researchers or the local government to make the best use of peatlands. Further research is needed to find out other aspects outside the engineering field to determine the characteristics of peat in Palangkaraya City, Central Kalimantan.